Hukum Administrasi dan Reformasi Birokrasi untuk Konsolidasi Demokrasi 2045 - Lely Mahartina Khoiru Ummah (Universitas Islam Negeri Islam Kiai Ageng Muhammad Besari Ponorogo, 2025)
Bureaucratic reform is a strategic agenda to realize a clean, transparent, and accountable government. In the context of Indonesia Emas 2045, the success of bureaucratic reform largely depends on the effectiveness of administrative law as an instrument of regulation, oversight, and legitimacy for governmental actions. This study examines how administrative law strengthens democratic consolidation through bureaucratic reform. This research employs a normative juridical method using statutory and conceptual approaches. The legal materials analyzed include primary legal sources (the 1945 Constitution, the Administrative Procedure Act, the Civil Service Act, and regulations related to bureaucratic reform and governance), secondary legal materials (scholarly literature, journals, and policy documents), and tertiary sources. The analysis is conducted qualitatively and descriptively, focusing on aspects of authority, accountability, and administrative control mechanisms within the framework of democracy toward 2045. The findings indicate that an effective model of administrative law requires strengthening democratic and accountable legal norms, reforming regulatory frameworks, and optimizing both internal and external control mechanisms. Without a solid administrative law foundation, Indonesia will face significant obstacles in realizing meaningful bureaucratic reform for the 2045 vision. This study concludes that bureaucratic reform requires an administrative law framework that is democratic, participatory, and responsive. Without a strong legal foundation, bureaucratic transformation will struggle to produce accountable and citizen-oriented governance. Strengthening administrative law is therefore a key pillar for achieving democratic consolidation and the broader agenda of Indonesia Emas 2045. Keywords: Administrative Law; Bureaucratic Reform; Democratic Consolidation; Governance; Indonesia Emas 2045.